¬PENGARUH DISIPLIN KERJA, LINGKUNGAN KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI (Studi pada Pegawai DINTANBUNNAKIKAN ( Dinas Pertanian, Perkebunan, Peternakan dan Perikanan ) Kabupaten Blora (Students' Journal of Economic and Management, 2016)
This study analyzed the effect of work discipline, work environment, organizational culture on employee performance. The object of research in this paper is the Office Dintanbunnakikan Blora district. Sampling technique in this research is using Simple Random Sampling (random) amount to 50 respondents in the sample data collection method using a questionnaire (questionnaire) by distributing questionnaires to the respondents in order to obtain information. The research objective formulated to determine the effect of work discipline, work environment, organizational culture on employee performance. Data were analyzed using factor analysis to test the validity of the question items, Cronbach alpha formula to test the reliability of each independent variable in the regression analysis test. The results of the research are: (1) the discipline of work and no significant negative influence on employee performance. (2) the work environment and no significant negative influence on employee performance. (3) organizational culture has a positive and significant impact on employee performance. Keywords: Work Discipline, Work Environment, Organizational Culture and Employee Performance